2015
DOI: 10.1080/01694243.2015.1101183
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired fibrillar adhesives: a review of analytical models and experimental evidence for adhesion enhancement by surface patterns

Abstract: Fibrillar structures are found on the attachment pads of insects and small reptiles. These structures enable exquisite conformation to rough surfaces, increase the number of van der Waals interactions between the structure and the target surface, and thus enhance adhesion.Biomimetic adhesives replicate this effect by patterning polymer films with micron-or submicron-sized protrusions. Numerical contact-mechanics models as well as experimental adhesion measurements have been reported for a variety of protrusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 83 publications
(170 reference statements)
1
22
0
Order By: Relevance
“…To this regard, several studies have been devoted to soft elastic contacts in presence of adhesion [11,[22][23][24][25], and specifically to the detachment process [26][27][28]. Experimental observations of insects and spiders [29][30][31] and theoretical studies [32][33][34] have made clear the crucial role played by highly flexible terminal spatula-shaped substructures attached to their legs, which finally allows them to easily climb on surfaces with different properties in terms of roughness and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…To this regard, several studies have been devoted to soft elastic contacts in presence of adhesion [11,[22][23][24][25], and specifically to the detachment process [26][27][28]. Experimental observations of insects and spiders [29][30][31] and theoretical studies [32][33][34] have made clear the crucial role played by highly flexible terminal spatula-shaped substructures attached to their legs, which finally allows them to easily climb on surfaces with different properties in terms of roughness and compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film-ended hairy adhesive structures have evolved independently in insects, arachnids and reptiles to secure their locomotion on substrates of arbitrary orientation, geometry and chemical composition [1]. Since it was revealed that terminal thin-film elements operate using intermolecular [2,3] and, possibly, also capillary [4,5] forces, which allowed these structures to be replicated with engineering materials, much effort has been put into the development of biomimetic adhesive surfaces [6,7]. This led to the introduction of mushroom-shaped microstructures [8,9] mimicking the hairs evolved in male leaf beetles for passive long-term attachment during pairing [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The result is exquisite contact between adhesive and substrate and, subsequently, strong adhesion from weak interactions such as hydrogen bonding, exemplified in biomimetic dry adhesives. 75 Such intimate contact is shown in histology micrographs 21,27,68 in Figure 5. Physical adhesion can be enhanced via entanglement of polymer chains and collagen fibers, 54 which can occur in such close proximity.…”
Section: ■ Discussionmentioning
confidence: 83%